The influence of historic land-use changes on hillslope erosion and sediment redistribution. (August 2016) - Larsen, Annegret; Robin, Vincent; Heckmann, Tobias; Fülling, Alexander; Larsen, Joshua R; Bork, Hans-Rudolf
Agricultural societies around the world have dramatically altered the natural landscape, particularly through accelerated soil erosion. The expansion of agricultural land use into steeper headwater areas during the Medieval period in central Europe is known to have caused large increases in soil erosion and sediment redistribution downstream. Although land-use practices changed and improved following this initial impact, it is currently unknown whether changes in land-use techniques also improved hillslope soil erosion and sediment redistribution rates. In this paper, we use a variety of techniques, including chrono-stratigraphy, wood charcoal analysis and a geostatistical model, to reconstruct land-use and erosion rates for the period spanning the Medieval Period to the present (1100–300 years ago) in a small headwater catchment in central Europe. Coupling land-use, hillslope erosion and sediment redistribution fluxes, we find the largest flux change occurs because of the initial deforestation at the beginning of the Medieval Period (1100 years ago). Following deforestation, we identified three main types of land-use techniques that were practised between 1100 and 300 years ago: Horticulture, cropping agriculture and rotational birch silviculture, the last of which represents the earliest evidence for this practice found in central Europe to date. However, we find only small differences in hillslope fluxes throughout the catchment despite the variable land-use techniques employed. This is because the land-use techniques primarily influenced and increased the hillslope sediment storage capacity rather than erosion rates directly, which is an important distinction to consider for future work attempting to link changes in human land use and hillslope erosion.